2012
DOI: 10.4274/tpa.823
|View full text |Cite
|
Sign up to set email alerts
|

Glanzmann trombastenisi: Cerrahpaşa Tıp Fakültesi deneyimi

Abstract: Aim: Glazmann thrombasthenia is a rare autosomal recessive disease characterized by a defect in platelet aggregation. Herein, we report the management of children with Glazmann thrombasthenia followed up at Cerrahpasa Medical Faculty Pediatric Hematology Department. Material and Method:The files of nineteen patients (42% girls, 58% boys; median age: 10 months) were retrospectively reviewed. Results: The median age of onset of bleeding symptoms was 9 months (2 weeks-24 months). All patients presented with easy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Since type 1 GT is seen in 52.2% of the GT patients, type 1 is considered to be the most common subgroup in Turkey, followed by type 3 and type 2 that is seen in 30.4% and 17.4%, respectively. The data confirmed to the previous studies from Turkey that type 1 GT was most common in Turkish patients [22,23]. Our results were in agreement with the result of Kannan et al study and Hassan et al study that revealed the highest frequency in type 1 GT (64% and 86%) followed by type 3 GT (24% and 11%) [24,25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Since type 1 GT is seen in 52.2% of the GT patients, type 1 is considered to be the most common subgroup in Turkey, followed by type 3 and type 2 that is seen in 30.4% and 17.4%, respectively. The data confirmed to the previous studies from Turkey that type 1 GT was most common in Turkish patients [22,23]. Our results were in agreement with the result of Kannan et al study and Hassan et al study that revealed the highest frequency in type 1 GT (64% and 86%) followed by type 3 GT (24% and 11%) [24,25].…”
Section: Discussionsupporting
confidence: 93%
“…No correlation between the levels of GP IIb/IIIa and severity of bleeding was reported [7,21]. In a study by Kutlubay et al in 2012, out of 15 Turkish GT cases 7, 6 and 2 of the patients were compatible with type 1, type 2 and type 3, respectively [22]. In 2015, Tokgöz et al reported that out of 20 Turkish GT patients, 18 and 2 cases were compatible with type 1 and type 2, respectively [23].…”
Section: Discussionmentioning
confidence: 99%